Kajian Ekonomi Usahatani Gembili (Dioscorea esculanta) di Kabupaten Muna Provinsi Sulawesi Tenggara - Ariani, Wa Ode Rachmasari; Geo, Laode (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
The sustainability of Indonesia's economic development is partly determined by the food security factor. The non-rice food crop diversification program is an effort to maintain food security. The Gembili is a type of non-rice food plant besides corn, cassava, sweet potato, peanuts, green beans, and taro. However, efforts to maintain food security through the development of the Gembili food crop agribusiness in Southeast Sulawesi are still not optimal. Muna Regency is one of the areas that have huge potential in the development of Gembili food crop farming. The purpose of this study was to determine the amount of income and financial feasibility of Gembili farming. This research was conducted in 2019 in Muna Regency in 2 (two) sub-districts, namely South Wakorumba District and Parigi District which were selected purposively. The study population was all 105 people of the Gembili plant and a sample of 32 people. The sampling method was stratified random (multi-stage sampling). The types of data used are primary data and secondary data. The data analysis method is descriptive quantitative. The results showed that the average income received by farmers was Rp. 299,625 per farmer per year. Financial feasibility is indicated by the R / C value, which is an average of 1.48, greater than 1 (one), meaning that the development of Gembili plants has been efficiently implemented. The processing of Gembili tubers into various preparations will certainly increase the economic value of the Gembili commodity. However, the local community sells Gembili tubers only in the form of commodities without being processed first, so the income received by farmers is classified as small. The local community has difficulty in developing Gembili farming due to various obstacles, namely the limited technology and production facilities and the difficulty in obtaining quality seeds. Empowerment, counseling, and mentoring as well as other concrete programs are needed to preserve and develop Gembili farming.